KEARIFAN LOKAL DALAM PENGELOLAAN SUMBERDAYA PERIKANAN - Nanang Widarmanto (Sabda: Jurnal Kajian Kebudayaan, 2018)
Indonesia has large potential fishery resources, both marine fisheries and inland public waters. The potential of existing fishing is expected to have an impact on the people’s beneficiaries. However its resources are open access and common property without the accompaniment surveillance which tends to encourage people at maximum utilization patterns and unsustainable. One approach to resource management effort, which is quite effective is the power of local construction. This paper aims to find out the various models of local construction in the management of fishery resources, especially in public waters. The writing method uses the desk or literature study. The study shows that the implementation of community-based management model is proven to deliver results quite effective and efficient. Management efficiency, which reduces conflict of fishermen and the sustainability of the resource is obtained from the management model based on local wisdom, which puts public participation as a key indicator in the implementation of resource management.